PENJATUHAN SANKSI DAN PERTANGGUNGJAWABAN TINDAK PIDANA KORPORASI DALAM TINDAK PIDANA KORUPSI - Asmui - - (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2023)
Nowadays, the development of perpetrators of criminal acts of corruption is not only perpetrate by individuals, but is also often committed by corporations. This behavior can be categorized as a corporate crime, so it has a very broad impact on society. Due to having such a broad impact, the Government began to regulate criminal sanctions for corporations involved in corruption cases. But in reality, there are still decisions that contradict the regulations that have been issued by the Government. One of them is in Decision No. 3/Pid.Sus-TPK/2018/PT.DKI, which is the focus of this research. In this study, the author uses the concept of accountability and the imposition of criminal sanctions against corporations. Based on the researcher's analysis, the verdict of the decision that imposes criminal sanctions on the management and the corporation may be carried out even though the corporation is not prosecuted by the Public Prosecutor. This was confirmed by the Supreme Court judge's conviction regarding Article 20 paragraph (1) of the Law. No. 31 of 1999 as amended by Law. No. 20 of 2001. When using the theory of corporations that act, the management and corporations are responsible, the verdict of Decision No. 3/Pid.Sus-TPK/2018/PT.DKI can also be justified.